2005
DOI: 10.1177/0363546504268036
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supplementary Tibial Fixation on Laxity Measurements after Anterior Cruciate Ligament Reconstruction with Hamstring Tendons in Female Patients

Abstract: Supplementary tibial fixation in female patients undergoing anterior cruciate ligament reconstruction with hamstring tendon graft in addition to a single-size screw significantly improves laxity measurements and clinical stability assessment 2 years after surgery. However, this improvement is at the cost of increased kneeling pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 24 publications
3
49
0
Order By: Relevance
“…1,2,10 If the surgeon feels that there was inadequate insertion torque during the insertion of the tapered screw or the patient has soft bone, then we recommend that supplemental tibial fixation be used. 10 Depending on the graft length, the protruding DGST tendons can be stapled below the tibial tunnel using a small barbed staple (Smith & Nephew Orthopaedics, Memphis, TN), or the sutures can be tied around a x-small nonbarbed staple or tibial fixation post (Smith & Nephew Endoscopy) (Fig. 6).…”
Section: Tibial Fixationmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2,10 If the surgeon feels that there was inadequate insertion torque during the insertion of the tapered screw or the patient has soft bone, then we recommend that supplemental tibial fixation be used. 10 Depending on the graft length, the protruding DGST tendons can be stapled below the tibial tunnel using a small barbed staple (Smith & Nephew Orthopaedics, Memphis, TN), or the sutures can be tied around a x-small nonbarbed staple or tibial fixation post (Smith & Nephew Endoscopy) (Fig. 6).…”
Section: Tibial Fixationmentioning
confidence: 99%
“…However, tibial fixation of hamstring tendon anterior cruciate ligament (ACL) grafts remains problematic. 1,2,8,10,14,15,18 Problems with tibial fixation result primarily from the lower bone mineral density of the proximal tibia, the fact that tibial fixation devices must resist shear forces applied parallel to the axis of the tibial bone tunnel, and the longer time required for soft tissue grafts to heal to bone. 1,2,9,10,16 Tibial fixation using screws and washers that anchor to the tibial cortex can address many of these issues; however, these implants are often prominent and often cause local skin irritation and pain requiring a second operation for removal.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Biomechanical studies showed that interference screws combined with additional indirect distal hamstring tendon fixation techniques can withstand much higher tearing forces than one type of fixation alone 4,5,6,7. However, additional metallic fixation devices (e.g., spike washers, post screws, and metal buttons) cause irritation of the soft tissue around the tibial cortical area, thus causing limitations such as metal removal 8,9. Therefore, we hypothesized that using BISs simultaneously with additional bioabsorbable suture anchor (BSA) devices could augment early fixation.…”
Section: Introductionmentioning
confidence: 99%